Association of soap use when bathing 18‐month‐old infants with the prevalence of allergic diseases at age 3 years: The Japan Environment and Children's Study. Issue 4 (17th April 2023) - Kato, Taisuke; Adachi, Yuichi; Tsuchida, Akiko; Matsumura, Kenta; Murakami, Shokei; Shimizu, Muneyuki; Wada, Takuya; Okabe, Hisao; Hashimoto, Koichi; Hosoya, Mitsuaki; Inadera, Hidekuni; ,
Abstract: Background: Atopic march is defined as the progression from atopic dermatitis (AD) during early life to other allergic diseases in later childhood. In a nationwide birth cohort study, the Japan Environment and Children's Study, we investigated the association of bathing habits, which are known to affect skin conditions, for infants with their later development of allergic diseases. Methods: Pregnant women who lived in 15 designated regional centers throughout Japan were recruited. We obtained information on bathing habits for their 18‐month‐old infants and the prevalence of allergic diseases when they were aged 3 years. Results: Data for 74, 349 children were analyzed. Most 18‐month‐old infants were bathed or showered almost every day. When they were divided into four groups according to the frequency of soap use during bathing (every time, most of the time, sometimes, and seldom), the risk of AD later at age 3 was shown to increase in association with a decreasing frequency of soap use [most of the time: adjusted odds ratio (aOR) 1.18, 95% confidence interval (CI) 1.05–1.34; sometimes: aOR 1.72, 95% CI 1.46–2.03; seldom: aOR 1.99, 95% CI 1.58–2.50], compared with soap use every time during bathing at 18 months of age. Similar results were obtained for food allergy but not for bronchial asthma. Conclusions: Frequent soap use when bathing 18‐month‐old infants was associated with a decreased risk of them developing allergic diseases at age 3. Further well‐designed clinical studies are warranted to determine an effective bathing regimen for preventing the development of allergic diseases.